Susceptibility Pattern of Multidrug Resistant Acinetobacter Baumannii among Intensive Care Unit Patients (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Acinetobacter baumannii Gram-negative, opportunistic bacterium is progressively cause hospital acquired infections specially intensive care unites. From May 2025 until September 2025, this study was cross-sectional and performed at Azady Teaching Hospital in Kirkuk, Iraq, to look at the frequency, age distribution, and antimicrobial resistance pattern of A. baumannii isolated from many clinical specimens. With the greatest isolation rates from urine and wound swabs (45.2% each), 31 (4.5%) of the 670 cultured samples turned out to be A. baumannii. The 45-55 year age range was particularly impacted. While colistin and tigecycline exhibited great efficacy (93.5% sensitivity), antibiotic ssensitivity testing conducted with the VITEK®2 compact system demonstrated high resistance to ampicillin (83.9%), trimethoprim/sulfamethoxazole (67.7%), and ciprofloxacin (64.5%). Resistance profiles differed statistically significantly among drugs (p < 0.0001). high level of XDR reported in isolates. These results underline how urgently antibiotic stewardship, infection control, and ongoing surveillance are needed to fight multidrug-resistant A. baumannii.